Paediatric sedation during upper gastrointestinal endoscopy: Comparison of propofol + ketamine vs sodium thiopental + fentanyl. Issue 6 (December 2018) - Takzare, Alireza; ,; Goudarzi, Mehrdad; Maleki, Anahid; Soltani, Alireza Ebrahim; Kaheh, Fariba; Arab, Sagar; Espahbodi, Ebrahim
No abstract available